Antioxidant Activity and Bioactive Compounds of Tropical Brown Algae Padina sp. from Bintan Island, Indonesia - Jelita Rahma Hidayati; Muhammad Syaifudien Bahry; Ita Karlina; Ervia Yudiati (Jurnal Kelautan Tropis, 2022)
Macroalgae is one of the marine resources that have the ability as an antioxidant. Its ability is obtained from bioactive compounds produced through secondary metabolism. One type of macroalgae that has the potential as an antioxidant is Padina sp. This study aims to analyze the content of bioactive compounds in Padina sp and determine their antioxidant activity using DPPH as free radicals. Padina sp. was taken from the Bintan waters and shade-dried for three days. Bioactive compounds were analyzed through phytochemical screening to determine the content of flavonoid compounds, steroids, triterpenoids, saponins, and tannins. Determination of antioxidant activity begins with measuring the maximum wavelength of DPPH at 400-800 nm and determining the incubation time of the sample and DPPH. Antioxidant activity was determined based on the value of Inhibition concentration (IC50) at a wavelength of 515.5 nm; total phenolic content was determined using gallic acid standard (725 nm); total flavonoid content was determined using quercetin standard (415 nm), chlorophyll a and carotenoids were selected to determine pigment content on the sample. The results showed that Padina sp. contains flavonoid compounds, steroids, and tannins. Extract of Padina sp. has a total phenolic content of 46.02 mg/GAE g; total flavonoid content of 35.36 mg/QE g; chlorophyll content of 9.18 mg/g; and carotenoid content of 26.46 µmol/g. Methanol extract of Padina sp. has an IC50 value of 92.17 ppm and is classified as a strong antioxidant.